OPTIMIZING DIGITAL LEARNING IN SCHOOLS THROUGH ARTIFICIAL INTELLIGENCE (AI) - Prasetya, Irwan Adhi; Wulandari, Mira; Sujatmiko, Wandi; Hermanto, Hermanto (Digulis: Jurnal Pengabdian Pada Masyarakat, 2024)
The advancement of information and communication technology (ICT) has significantly impacted various aspects of life, including education. One of the latest innovations with great potential for the education sector is Artificial Intelligence (AI). AI refers to systems that can mimic human cognitive functions such as learning, thinking, and problem-solving. In the context of digital schools, AI can be implemented through adaptive learning systems that adjust content and teaching methods to meet the needs and abilities of individual students. This community service activity aims to apply AI technology to the learning process in schools. Held on August 14, 2024, at SMA Negeri 8 Pontianak, the activity involves three phases: preparation, implementation before participants, and the core activities, including QA sessions and discussions led by faculty members. The training, attended by 28 students, was conducted by the lecturers. Results show that implementing AI in education enhances the quality of learning in digital school environments by providing a more personalized and adaptive learning experience. The training was successful, focusing on the direct demonstration of AI-based adaptive learning systems. In conclusion, the use of AI in education can improve the effectiveness and personalization of learning and was carried out smoothly and effectively.